Concessive constructions with ‘por mais que’: a functional-discourse approach - Fontes, Michel Gustavo (2022)
Following Functional Discourse Grammar model principles (Hengeveld & Mackenzie, 2008), this paper describes concessive constructions with the conjunction por mais que. Using contemporary Portuguese data, from Corpus do Português (Davies & Ferreira, 2016), this investigation pursues two specific objectives: (i) determining the status of por mais que considering a set of FDG proposals concerning the lexical/grammatical status of adverbial conjunctions; and (ii) mapping, based on FDG levels and layer, the different concessive relations signaled by this conjunction in articulating clauses. It is argued that por mais que is a Lexical Conjunction, analyzed, at Representational Level, as a one-place Configurational Property, and that it articulates three types of concessive relations: factual concessive, conditional-concessive and restrictive concessive.